Pore channel functionalized covalent organic framework oxygen evolution catalyst and preparation method thereof

By introducing ferrocene into the covalent organic frame material TFp-BPy to form the composite frame structure FRC@TFp-BPy, the problems of uneven distribution of active sites and insufficient conductivity of COFs materials in OER catalysts are solved, and the problem of inequality and insufficient conductivity of COFs materials is achieved. Efficient catalytic performance of oxidation reaction and low-cost preparation process.

CN119162602APending Publication Date: 2024-12-20ZHONGBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411455077.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing covalent organic framework (COFs) materials have problems with uneven distribution of active sites, insufficient conductivity and reaction catalytic activity in the oxidation reaction (OER) catalysts, and their preparation is complex and costly.

Method used

By introducing the organometallic compound ferrocene into the pores of the covalent organic frame material TFp-BPy in an impregnation manner, a composite frame structure FRC@TFp-BPy was formed, and combined with ultrasonic crushing treatment and negative pressure immersion technology, an excellent structural stability was prepared. and catalysts for oxygen evolution electrocatalytic properties.

Benefits of technology

It improves the uniformity of the active site distribution, conductivity and reaction catalytic activity of the catalyst, reduces production costs, and simplifies the preparation process, achieves good structural stability and oxygen evolution catalytic performance, and is suitable for electrolyzing hydrogen production reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162602A_ABST
    Figure CN119162602A_ABST
Patent Text Reader

Abstract

The invention relates to a pore channel functionalized covalent organic framework oxygen evolution catalyst which is prepared by the following steps: by taking a covalent organic framework material TFp-BPy as a framework, introducing an organic metal compound ferrocene containing a catalytic site into a pore channel of the TFp-BPy in a dipping manner; the formed composite frame structure FRC (at) TFp-BPy: # imgabs0 # is shown in a structural formula (I). According to the invention, an organic metal compound ferrocene containing a catalytic site is introduced into a pore channel of a TFp-BPy frame material, so that the novel composite frame structure with excellent structural stability and oxygen evolution electro-catalytic performance is prepared; the catalyst can be used as an oxygen evolution catalyst in a water electrolysis hydrogen production reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy materials and relates to a catalyst for hydrogen evolution from water electrolysis, and in particular to a pore-functionalized oxygen evolution catalyst based on a covalent organic framework structure and a preparation method thereof. Background Art

[0002] Global energy demand has led to rising energy costs and negative impacts on the environment. As a clean energy, hydrogen energy is seen as an ideal energy solution due to its zero carbon emissions and high energy density, which can help reduce dependence on fossil fuels, reduce greenhouse gas emissions, and combat climate change. The high energy density of hydrogen energy also makes it have application potential in many fields and is expected to play a key role in the global energy transformation.

[0003] Hydrogen production by water electrolysis is an environmentally friendly green hydrogen production technology that uses renewable energy to decompose water into hydrogen and oxygen to achieve zero carbon emissions. It is easy to operate and maintain, and the hydrogen produced is of high purity, which has a good development prospect. At the technical level, hydrogen production by water electrolysis has achieved the use of low-cost non-precious metal catalysts and efficient and stable ion exchange membranes, which greatly reduces the cost of raw materials.

[0004] The production of hydrogen by electrolysis of water involves two key half-reactions: the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). To improve the efficiency of HER, commonly used catalysts include precious metals such as platinum, iridium, and ruthenium, as well as non-precious metals such as nickel, cobalt and their oxides or sulfides. Current research is committed to finding catalyst materials with lower costs and more abundant reserves, such as transition metal sulfides, selenides, phosphides, and catalysts derived from metal organic frameworks. These new materials show good activity and stability, which will help reduce the cost of hydrogen production and promote the commercialization of water electrolysis technology. At the same time, OER involves the transfer of four electrons. The energy accumulation of this process leads to a large overpotential and a slow reaction rate, which becomes the main obstacle to improving the efficiency of water electrolysis. In industrial applications, the development of oxygen evolution catalysts that are both efficient and stable is a key challenge.

[0005] Covalent organic frameworks (COFs) are porous crystalline materials formed by covalently connecting light elements such as C, B, O and N. They are light in weight, low in density, high in specific surface area, regular and stable in structure, easy to be functionalized, and have good pore structure, chemical stability and thermodynamic stability. These characteristics enable them to form coordination with specific atoms in the organic framework by utilizing the constraint effect, provide a variable coordination platform for isolated metal atoms, and adjust the coordination environment of metal atoms; in addition, they can also achieve composite with other materials or design core-shell structures while maintaining the pore structure of the material. Such design strategies are helpful for the development of new materials with specific functions and properties, and show great potential for application in many fields such as gas storage and separation, catalysis, sensing, energy storage, and photoelectric conversion.

[0006] Although COFs materials have made a lot of progress in the field of electrocatalysis, there are still some problems to be solved. COFs materials without metal coordination lack active sites, resulting in low catalytic activity, which restricts their development in OER catalysts. Modifying COFs by impregnating metal sites in the pores to improve their performance is of great significance for improving the oxygen evolution catalytic performance of OER catalysts.

[0007] Zhu Xiaolun et al. (Bimetal-anchored covalent organic frameworks derivatives for efficient alkaline electrolyte oxygen evolution. Journal of Alloys and Compounds 2022, 924, 166442.) A covalent organic framework (COF)-derived catalyst anchored by pyrolysis-active bimetallic (Fe / Co) was developed, in which COF-derived carbon served as a support for anchoring active bimetallic Fe / Co nanoparticles. The COF-derived catalyst exhibited excellent OER performance with a low overpotential of 288 mV, outperforming commercial RuO2 and most oxygen evolution catalysts due to its rich nitrogen content, high micropore and mesopore volume, and good electrolyte permeability.

[0008] Shyamapada Nandi et al. (Low Band Gap Benzimidazole COF Supported Ni3N asHighly Active OER Catalyst. ADVANC EDENERGY MATERIAL 2016, 6, 1601189.) Ni and N nanoparticles were loaded on benzimidazole COF to form a composite for oxygen evolution reaction. The composite has a record low overpotential of 230 mV @ 10 mA cm -2 Oxidized alkaline water.

[0009] Liu Xin et al. (Covalent Organic Frameworks Composites Containing BipyridineMetal Complex for Oxygen Evolution and Methane Conversion. Molecules 2022,27, 5193.) designed and synthesized a series of novel bipyridine-containing multimetallic complex COFs composite materials, among which the optimized bimetallic composite material Co 0.75 Fe 0.25 @COF-TB has the advantages of low overpotential and good stability, and exhibits excellent electrocatalytic OER activity with a current density of 10 mA cm in 1 M KOH solution. −2 , overpotential 331mV.

[0010] The above-mentioned COFs composite catalysts all introduce metal ions by means of coordination bonds. Although they perform well in terms of chemical stability and maintaining pore structure of the composite materials, they still have deficiencies in terms of uniformity of distribution of active sites in the composite materials, electrical conductivity, and catalytic activity and selectivity for specific reactions. In addition, their preparation may be more complicated and the production cost may be higher. Summary of the invention

[0011] The purpose of the present invention is to provide a pore-functionalized covalent organic framework oxygen evolution catalyst and a preparation method thereof. Based on the composite framework structure of the constructed catalyst, the oxygen evolution catalyst has both excellent structural stability and good oxygen evolution catalytic performance.

[0012] The pore-functionalized covalent organic framework oxygen evolution catalyst of the present invention uses the covalent organic framework material TFp-BPy as a framework, and introduces the organic metal compound ferrocene containing catalytic sites into the pores of TFp-BPy by impregnation to form a composite framework structure FRC@TFp-BPy having a structure shown in the following structural formula (I):

[0013]

[0014] The pore-functionalized covalent organic framework oxygen evolution catalyst of the present invention is obtained by confining the organic metal compound ferrocene in the pores of the TFp-BPy framework by utilizing the pressure difference between the inside and outside of the pores of the TFp-BPy framework. The catalyst is a reddish brown powder and is insoluble in organic solvents.

[0015] Furthermore, in the pore-functionalized covalent organic framework oxygen evolution catalyst of the present invention, the mass ratio of the TFp-BPy framework to ferrocene is 1:5-190.

[0016] Furthermore, the mass ratio of the TFp-BPy framework to ferrocene is more preferably 1:90-120.

[0017] On the other hand, the present invention also provides a method for preparing the pore-functionalized covalent organic framework oxygen evolution catalyst, specifically, the covalent organic framework material TFp-BPy is preheated at 90-100° C. under a vacuum state, and then a methanol solution of the organic metal compound ferrocene is injected, and negative pressure impregnation is performed under a vacuum state to fully immerse the ferrocene in the pores of TFp-BPy, and after drying, a composite framework structure shown in structural formula (I) is formed.

[0018] Wherein, the preheating treatment is carried out in a continuous vacuum environment, and the preheating treatment time is preferably 24 to 30 hours.

[0019] Furthermore, the negative pressure impregnation is carried out at 40-60° C., and the negative pressure impregnation time is preferably 30-48 hours.

[0020] It should be noted that the vacuum environment described in the present invention is not a complete vacuum environment, but a continuous negative pressure environment obtained by intermittent vacuuming by a vacuum pump.

[0021] In order to facilitate negative pressure impregnation of the covalent organic framework material TFp-BPy, the present invention also preferably performs ultrasonic crushing on the TFp-BPy, specifically, the covalent organic framework material TFp-BPy is dispersed in a dimethylformamide or N-methylpyrrolidone solvent system to form a suspension, and the suspension is crushed at low temperature using an ultrasonic cell crusher, and the solvent is removed to obtain a refined TFp-BPy material. The refined TFp-BPy material is more conducive to subsequent pore impregnation modification.

[0022] More specifically, the present invention preferably uses an ultrasonic cell disruptor with a power of 200 to 300 W to disrupt the suspension at a low temperature of 0 to 30° C., and the preferred disruption treatment time is 1.5 to 3 hours.

[0023] Furthermore, the TFp-BPy used as the framework in the present invention may be TFp-BPy prepared by various reported preparation methods, and the present invention has no particular limitation thereto.

[0024] However, preferably, the TFp-BPy described in the present invention can be a TFp-BPy framework structure obtained by condensing trialdehyde pyrogallol and 5,5'-diamino-2,2'-bipyridine as raw materials in an N,N-dimethylaniline / 1,2-dichlorobenzene solvent system in an acetic acid aqueous solution.

[0025] Specifically, the molar ratio of trialdehyde phloroglucinol to 5,5'-diamino-2,2'-bipyridine is preferably 1:1.5-2.

[0026] The present invention successfully prepared a new composite framework structure FRC@TFp-BPy with excellent structural stability and oxygen evolution electrocatalytic performance by introducing the organic metal compound ferrocene containing catalytic sites into the pores of the TFp-BPy framework material. The FRC@TFp-BPy can be used as an oxygen evolution catalyst in the hydrogen production reaction by electrolysis of water.

[0027] The present invention peels off the multi-layer nanostructured TFp-BPy into a single-layer nanostructure, and confines the organic metal compound ferrocene in the pores of TFp-BPy by negative pressure impregnation, thereby constructing a nano-impregnated "ferrocene" COFs structure oxygen evolution catalyst FRC@TFp-BPy. Compared with the unmodified TFp-BPy, not only the basic electrocatalytic performance of the catalyst is improved, but also compared with the composite COFs material into which metal ions are introduced by coordination bonds, the uniformity of active site distribution, electrical conductivity, and reaction catalytic activity and selectivity are greatly improved, thereby achieving both good structural stability and oxygen evolution catalytic performance.

[0028] The preparation method of the pore impregnation modified FRC@TFp-BPy composite framework structure of the present invention is simple, the production cost is low, it is easy to scale up production, and it shows broad application potential in multiple fields such as gas storage, separation, catalysis and sensing. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the X-ray photoelectron spectroscopy (XPS) comparison diagram of FRC@TFp-BPy and TFp-BPy.

[0030] Figure 2 This is a comparison chart of infrared spectra (FTIR) of FRC@TFp-BPy and TFp-BPy.

[0031] Figure 3 are the transmission electron microscopy (TEM) images of FRC@TFp-BPy and TFp-BPy.

[0032] Figure 4 It is the cyclic voltammetry (CV) curve of FRC@TFp-BPy and TFp-BPy.

[0033] Figure 5 is the linear sweep voltammetry (LSV) comparison curve (OER) of FRC@TFp-BPy and TFp-BPy.

[0034] Figure 6is the linear sweep voltammetry (LSV) comparison curve (HER) of FRC@TFp-BPy and TFp-BPy.

[0035] Figure 7 It is the comparison curve of Tafel slope between FRC@TFp-BPy and TFp-BPy.

[0036] Figure 8 This is the electrochemical impedance comparison curve between FRC@TFp-BPy and TFp-BPy.

[0037] Fig. 9 It is the comparison curve of double layer capacitance between FRC@TFp-BPy and TFp-BPy. Implementation

[0038] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.

[0039] The production processes, experimental methods or detection methods involved in the embodiments and comparative examples of the present invention are all conventional methods in the prior art unless otherwise specified, and their names and / or abbreviations are all conventional names in the field and are very clear and unambiguous in the relevant application fields. Those skilled in the art can understand the conventional process steps based on the names and apply the corresponding equipment to implement them according to conventional conditions or the conditions recommended by the manufacturer.

[0040] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art. Example

[0041] Example 1

[0042] Trialdehyde phloroglucinol (208 mg, 1 mmol) and 5,5'-diamino-2,2'-bipyridine (279 mg, 1.5 mmol) were dissolved in 20 ml of N,N-dimethylaniline / 1,2-dichlorobenzene mixed solution (1:1 v / v), placed in a 50 ml Teflon-lined autoclave, and ultrasonicated for 5 min to make it uniformly dispersed. Then, 2.7 ml of 6 mol L -1 The mixture was stirred with a magnetic stirrer for 2 h, sealed, and heated to 120 °C for 72 h.

[0043] The precipitate was collected by centrifugation, washed with anhydrous tetrahydrofuran (6×4 ml) and acetone (3×4 ml), respectively, and dried under vacuum at 80°C overnight to obtain orange-red TFp-Bpy with a yield of 65%.

[0044] Example 2

[0045] The TFp-Bpy prepared in Example 1 was ground into powder and dispersed in 50 ml of dimethylformamide solvent to form a suspension. The suspension temperature was kept at 0°C by circulating cooling. An ultrasonic cell disruptor was used to disrupt the suspension for 1.5 hours at a power of 200 W. During this period, the ultrasonic on / off time was set to 2s and 3s respectively.

[0046] The suspension was vacuum filtered, washed with methanol (15×3 ml), and dried overnight at 80°C in vacuum to obtain a finer orange-red TFp-Bpy powder.

[0047] Weigh 30 mg of the above-mentioned dried TFp-Bpy powder into a reaction bottle and evacuate for 2 minutes. Repeat the operation three times or more, then heat the reaction bottle to 90°C in an oil bath for 30 hours, during which time the evacuation is repeated every 2 hours.

[0048] Weigh ferrocene (0.274 g, 1.5 mmol) and dissolve it in 2 ml of anhydrous methanol to prepare an impregnation reagent, which is slowly injected into the reaction bottle using a disposable syringe and reacted at 40°C for 36 h.

[0049] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean Petri dish, and dried overnight at 80 °C in vacuum to obtain a deep red product FRC@TFp-Bpy with a yield of 85%.

[0050] Example 3

[0051] The TFp-BPy prepared in Example 1 was ground into powder and dispersed in 50 ml of dimethylformamide solvent to form a suspension. The suspension temperature was kept at 0°C by circulating cooling. An ultrasonic cell disruptor was used to disrupt the suspension at a power of 200 W for 1.5 h, during which the ultrasonic on / off time was set to 2 s and 3 s respectively.

[0052] The suspension was vacuum filtered, washed with methanol (15 × 3 ml), and dried overnight at 80 °C in vacuum to obtain a finer orange-red TFp-BPy powder.

[0053] Weigh 30 mg of the above-mentioned dried TFp-BPy powder into a reaction bottle and evacuate the solution for 2 min. Repeat the operation three times or more. Then, heat the reaction bottle to 95°C in an oil bath for 24 h, during which the evacuation is repeated every 2 h.

[0054] Weigh ferrocene (2.85 g, 15 mmol) and dissolve it in 10 ml of anhydrous methanol to prepare the impregnation reagent, which is slowly injected into the reaction bottle using a disposable syringe and reacted at 40°C for 36 h.

[0055] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean Petri dish, and dried overnight in vacuum at 80 °C to obtain a deep red product FRC@TFp-BPy with a yield of 75%.

[0056] Example 4

[0057] The TFp-BPy prepared in Example 1 was ground into powder and dispersed in 50 ml of dimethylformamide solvent to form a suspension. The suspension temperature was kept at 0°C by circulating cooling. An ultrasonic cell disruptor was used to disrupt the suspension at a power of 200 W for 1.5 h, during which the ultrasonic on / off time was set to 2 s and 3 s respectively.

[0058] The suspension was vacuum filtered, washed with methanol (15 × 3 ml), and dried overnight at 80 °C in vacuum to obtain a finer orange-red TFp-BPy powder.

[0059] Weigh 30 mg of the above-mentioned dried TFp-BPy powder into a reaction bottle and evacuate the solution for 2 min. Repeat the operation three times or more. Then, heat the reaction bottle to 90°C in an oil bath for 30 h, during which the evacuation is repeated every 2 h.

[0060] Weigh ferrocene (5.69 g, 30 mmol) and dissolve it in 20 ml of anhydrous methanol to prepare an impregnation reagent, which is slowly injected into the reaction bottle using a disposable syringe and reacted at 40°C for 36 h.

[0061] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean Petri dish, and dried overnight under vacuum at 80 °C to obtain a deep red product FRC@TFp-BPy with a yield of 80%.

[0062] Example 5

[0063] The TFp-Bpy prepared in Example 1 was ground into powder and dispersed in 50 ml of N-methylpyrrolidone solvent to form a suspension. The suspension temperature was kept at 0°C by circulating cooling. An ultrasonic cell disruptor was used to disrupt the suspension for 3 h at a power of 200 W, during which the ultrasonic on / off time was set to 2 s and 2 s respectively.

[0064] The suspension was vacuum filtered, washed with methanol (15 × 3 ml), and dried overnight at 80 °C in vacuum to obtain a finer orange-red TFp-BPy powder.

[0065] Weigh 30 mg of the above-mentioned dried TFp-BPy powder into a reaction bottle and evacuate for 2 minutes. Repeat the operation three times or more, and then heat the reaction bottle to 100°C in an oil bath for 24 hours, during which the evacuation is repeated every 2 hours.

[0066] Weigh ferrocene (2.85 g, 15 mmol) and dissolve it in 10 ml of anhydrous methanol to prepare the impregnation reagent, which is slowly injected into the reaction bottle using a disposable syringe and reacted at 40°C for 48 h.

[0067] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean Petri dish, and dried overnight under vacuum at 80 °C to obtain a deep red product FRC@TFp-BPy with a yield of 80%.

[0068] Example 6

[0069] The TFp-BPy prepared in Example 1 was ground into powder and dispersed in 50 ml of N-methylpyrrolidone solvent to form a suspension. The suspension temperature was kept at 0°C by circulating cooling. The suspension was crushed for 3 h using an ultrasonic cell disruptor at a power of 150 W, during which the ultrasonic on / off time was set to 2 s and 2 s respectively.

[0070] The suspension was vacuum filtered, washed with methanol (15 × 3 ml), and dried overnight at 80 °C in vacuum to obtain a finer orange-red TFp-BPy powder.

[0071] Weigh 30 mg of the above-mentioned dried TFp-BPy powder into a reaction bottle and evacuate for 2 minutes. Repeat the operation three times or more, and then heat the reaction bottle to 100°C in an oil bath for 24 hours, during which the evacuation is repeated every 2 hours.

[0072] Weigh ferrocene (2.86 g, 15 mmol) and dissolve it in 10 ml of anhydrous methanol to prepare the impregnation reagent, which is slowly injected into the reaction bottle using a disposable syringe and reacted at 60°C for 30 h.

[0073] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean Petri dish, and dried overnight in vacuum at 80 °C to obtain a deep red product FRC@TFp-BPy with a yield of 78%.

[0074] Application Example 1

[0075] A nickel foam sheet with a size of 1.5×2 cm was treated with 3 mol / L hydrochloric acid solution, ultrapure water and anhydrous ethanol for 15 min each to remove surface oxides and organic molecules, and then dried in vacuum at 60°C for 6 h.

[0076] Weigh 5 mg of the TFp-Bpy powder refined in Example 2, place it in a mortar containing 950 μl of anhydrous ethanol and 25 μl of 5wt% Nafion, grind it for 40 min to form an ink-like state, pick it up with a brush and evenly apply it on the foam nickel sheet, apply it 5 times in total, ensure that the coverage area of ​​the foam nickel sheet reaches 3 cm², and vacuum dry it for 6 h to prepare a TFP-BPy catalyst-modified working electrode.

[0077] The mass of the nickel foam sheet before and after coating was weighed, and the catalyst loading of the working electrode was calculated to be 1 mg cm -2 .

[0078] Application Example 2

[0079] A nickel foam sheet with a size of 1.5×2 cm was treated with 3 mol / L hydrochloric acid solution, ultrapure water and anhydrous ethanol for 15 min each to remove surface oxides and organic molecules, and then dried in vacuum at 60°C for 6 h.

[0080] 5 mg of the FRC@TFp-Bpy catalyst prepared in Example 2 was weighed and placed in a mortar containing 950 μl of anhydrous ethanol and 25 μl of 5 wt% Nafion. It was ground for 40 min to form an ink-like state. After being picked up with a brush, it was evenly applied on the nickel foam sheet for 5 times to ensure that the coverage area of ​​the nickel foam sheet reached 3 cm². The catalyst was vacuum dried for 6 h to obtain a FRC@TFP-BPy catalyst-modified working electrode.

[0081] The mass of the nickel foam sheet before and after coating was weighed, and the catalyst loading of the working electrode was calculated to be 1 mg cm -2 .

[0082] The basic structure characterization of the TFP-BPy and FRC@TFP-BPy catalysts loaded on the working electrode prepared in the above-mentioned application examples 1 and 2 is as follows: Figures 1 to 3 As shown, relevant electrochemical performance tests were also carried out, and the results are shown in Figures 4 to 9 .

[0083] XPS is a characterization method based on the principle of photoelectric effect. When the surface of a material is irradiated by X-rays, the photons of the rays interact with the atoms on the surface of the material, exciting the electrons on the surface of the material to a higher energy level. By analyzing the energy and number of these excited electrons, information such as the chemical composition, chemical state, and spatial distribution of elements on the surface of the material can be obtained. Figure 1 Compared with the electronic energy spectrum of TFP-BPy, the Fe 2p The peaks demonstrate the successful introduction of ferrocene.

[0084] Fourier transform infrared spectroscopy (FTIR) can be used to effectively identify the structure of substances. Figure 2 The FTIR analysis results showed that 3094cm -1 is the CH stretching vibration peak on the cyclopentadienyl ring; 1106cm -1 The CC deformation vibration peak on the cyclopentadienyl ring; 784cm -1 The out-of-plane deformation vibration peak of CH on the cyclopentadienyl ring; 475cm -1 is the stretching vibration of ferrocene and Fe. These results further confirm that ferrocene has been successfully impregnated into the pores of TFP-BPy.

[0085] and then, Figure 3 In the TEM analysis results, the spherical clusters of the original TFP-BPy on the left are hollow, but the morphology of FRC@TFP-BPy is almost not damaged during the pore functionalization modification process. However, due to the introduction of ferrocene, the TEM image of FRC@TFP-BPy becomes darker than that of TFP-BPy, confirming the presence of the organometallic compound ferrocene in the pores.

[0086] All electrochemical tests were performed on a standard three-electrode cell using an LViumSTAT electrochemical workstation. The catalyst was used as the working electrode (working electrode area 1 mA cm -2 ), platinum sheet as counter electrode, mercury oxide (Hg / HgO) electrode as reference electrode (reference electrode was calibrated before use), the electrochemical properties of the prepared catalysts such as LSV, EIS, CV, Tafel were tested in 1M KOH electrolyte, and the OER performance of the catalysts at room temperature was studied and evaluated. All polarization curves were iR corrected, and the recorded potentials were converted to reversible hydrogen potentials, the formula is as follows (pH=14):

[0087] E RHE = E Hg / HgO +0.098+0.059× pH

[0088] Before the formal test, cyclic voltammetry was used in the potential range of -0.2 to -0.1 V vs RHE at 50 mV s -1 The catalyst working electrode was electrochemically activated for 100 cycles at a scan rate of 1.5 to reach a stable state.

[0089] Figure 4 The results show that the TFP-BPy (left) and FRC@TFP-BPy (right) have different scan rates (20 mV s -1 , 40mV s -1 , 60mV s -1, 80mV s -1 , 100mV s -1 ) under the CV curve. Take the absolute value of the current density difference at the intermediate potential ΔJ ,by ΔJ Plotted against the corresponding scan rate, half of the slope is the double layer capacitance Cdl. The larger the capacitance, the more active sites per unit area, which is more conducive to the oxygen evolution reaction.

[0090] Linear voltammetry (LSV) is often used to evaluate the OER / HER performance of catalysts. The LSV curve changes the electrode potential and records the change in current density at a fixed scan rate to obtain the activity of the catalyst at different potentials. Overpotential (η) is a key parameter that reflects the polarization degree and efficiency of the catalyst when current passes through it, that is, the difficulty of the electron transfer reaction on the catalyst surface. The smaller the η value, the lower the additional potential is required to drive the same current density, and the better the OER / HER performance.

[0091] The oxygen evolution overpotential η(OER) value is calculated as η(OER)= E RHE -1.23, where 1.23 V is the standard potential of OER, the threshold for oxygen evolution at the lower electrode of the reversible hydrogen electrode, and the current density is 10 mA cm −2 It is used as a benchmark threshold for evaluating electrocatalytic performance. The standard potential of HER is defined as 0 V, E RHE is the actual potential relative to the reversible hydrogen electrode, so the hydrogen evolution overpotential η(HER)=| E RHE |.

[0092] Figure 5 The LSV curves were used to evaluate the catalyst material at 5 mV s -1 OER performance under scan rate. In 1 M KOH alkaline solution, the FRC@TFP-BPy catalyst modified electrode has better OER catalytic activity than TFP-BPy. -2 When , the overpotential of the FRC@TFP-BPy catalyst is 209.8 mV, which is lower than the overpotential of TFP-BPy 348 mV, indicating that the impregnation of organometallic compounds containing ferrocene improves the catalytic performance of OER.

[0093] Figure 6 The LSV curve was used to evaluate the catalyst material at -2.5 mV s -1 HER performance under scan rate. In 1 M KOH alkaline solution, the FRC@TFP-BPy catalyst modified electrode has better HER catalytic activity than TFP-BPy. -2When , the overpotential of FRC@TFP-BPy catalyst is 185 mV, which is lower than the overpotential of TFP-BPy 222 mV.

[0094] Figure 7 The Tafel slope in comes from Figure 5 The LSV measurement shows the relationship between η and the logarithm of the current density. According to the Tafel equation, the Tafel slope of the FRC@TFP-BPy catalyst is 291 mV dec -1 , lower than TFP-BPy (298mV dec -1 ). The lower the Tafel slope value, the higher the electrocatalytic activity.

[0095] Figure 8 The electrochemical impedance spectroscopy (EIS) test analysis was performed at 1.56V vs. RHE, with a frequency of 100,000Hz to 0.01Hz and an amplitude of 10mV to evaluate the charge transfer ability of the material. The smaller the electrochemical impedance, the stronger the charge transfer ability. The charge transfer resistance of FRC@TFP-BPy in the figure is low, indicating that FRC@TFP-BPy has good conductivity, which helps to improve its OER performance.

[0096] The electrochemically active surface area is a key parameter, and its measurement is crucial to evaluating the performance of catalysts and optimizing the design of electrochemical catalysts. Double layer capacitance (Cdl) is a common method to measure the electrochemically active surface area, which reflects the surface area of ​​the electrode in contact with the electrolyte and can provide information about the number of active sites on the catalyst. Materials with the largest double layer capacitance indicate a higher electrochemical specific surface area, which means that more catalytically active sites are exposed, which may increase the rate and efficiency of the electrocatalytic reaction. However, this method is not absolutely accurate and has some limitations and assumptions. For example, in reality, there may be non-uniformity and inactive areas on the electrode surface that affect the Cdl measurement results. Figure 4 The CV curve and Fig. 9 From the Cdl graph, we can see that the double layer capacitance of FRC@TFP-BPy is almost the same as that of TFP-BPy, which means that they have similar performance in terms of electrochemical active surface area.

[0097] The above results indicate that the appropriate amount of organometallic compound pore impregnation modification can provide more available active surface area for electrolyte penetration and improve the catalytic activity of the catalyst.

[0098] At the same time, the electrochemical performance of the catalyst of Example 2 is compared with the performance indicators of COF catalysts reported in some literature in Table 1 below. It can be seen that the catalytic performance of FRC@TFp-BPy is better than that of several coordinated COFs that have been published.

[0099]

[0100] [1]. Xiaolun Zhu, Nan He, Junxia Ding, Ruimei Yue, Simin He, Wentong Liu, Nijuan Liu, Ruibin Guo, Zunli Mo, Bimetal-anchored covalent organic frameworks derivatives for efficient alkaline electrolyte oxygen evolution. Journal of Alloys and Compounds , 2022, 924, 166442.

[0101] [2]. Shyamapada, Nandi, Santosh, Kumar, Singh, & Dinesh, et al., Lowband gap benzimidazole COF supported Ni3N as highly active OER catalyst. Advanced Energy Materials , 2016, 6, 1601189.

[0102] [3] Liu, X. Feng, L. Li, Y. Xia, T. Sui, Z. Chen, Q. Covalent OrganicFrameworks Composites Containing Bipyridine Metal Complex for OxygenEvolution and Methane Conversion. Molecules , 2022, 27, 5193.

[0103] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Those skilled in the art may make various changes, modifications, substitutions and variations to these embodiments without departing from the principles and purpose of the present invention, which shall all be included in the protection scope of the present invention.

Claims

1. A pore-functionalized covalent organic framework oxygen evolution catalyst, which uses a covalent organic framework material TFp-BPy as a framework, and introduces an organic metal compound ferrocene containing catalytic sites into the TFp-BPy pores by impregnation to form a composite framework structure FRC@TFp-BPy having a structure shown in the following structural formula (I): 。 2. The pore-functionalized covalent organic framework oxygen evolution catalyst according to claim 1, wherein the mass ratio of the TFp-Bpy framework to ferrocene in the catalyst is 1:5-190.

3. The pore-functionalized covalent organic framework oxygen evolution catalyst according to claim 2, characterized in that The mass ratio of TFp-Bpy framework to ferrocene is 1:90-120.

4. The method for preparing the pore-functionalized covalent organic framework oxygen evolution catalyst according to claim 1 is to preheat the covalent organic framework material TFp-Bpy at 90-100° C. under vacuum, inject a methanol solution of the organic metal compound ferrocene, perform negative pressure impregnation under vacuum, so that the ferrocene is fully impregnated in the pores of TFp-Bpy, and form a composite framework structure shown in structural formula (I) after drying.

5. The preparation method according to claim 4, characterized in that Preheat treatment in a continuous vacuum environment for 24 to 30 hours.

6. The preparation method according to claim 4, characterized in that Immerse under negative pressure at 40-45°C for 30-48 hours.

7. The preparation method according to claim 4, characterized in that Before the preheating treatment, TFp-Bpy is dispersed in a dimethylformamide or N-methylpyrrolidone solvent system to form a suspension, and an ultrasonic cell disruptor is used to perform ultrasonic disruption treatment to remove the solvent to obtain a refined TFp-Bpy material.

8. The preparation method according to claim 7, characterized in that The suspension is broken at a low temperature of 0 to 30°C using an ultrasonic cell disruptor with a power of 200 to 300W.

9. The preparation method according to claim 8, characterized in that Crushing 1.5~3h。 10. Use of the pore-functionalized covalent organic framework oxygen evolution catalyst according to claim 1 as a catalyst for producing hydrogen by electrolysis of water.